Unpacking "two-way" workplace integration of internationally educated nurses - ZUBEIDA RAMJI; JOSEPHINE ETOWA; ISABELLE ST-PIERRE (University of Ottawa, 2019)
This paper presents findings from a qualitative case study that explored long term integration of internationally educated nurses in an Ontario healthcare facility. Using critical social theory as the philosophical underpinnings for this research, we selected the case based on the hospital's history of employing and supporting internationally educated professionals. Data sources included: documents review, twenty-eight interviews, socio-demographic survey and five focus groups involving IENs and other stakeholders. An overarching theme points to a 'two-way' notion of workplace integration whereby efforts are required on the part of the employer as well as the IENs. An in-depth analysis of the data reveals sub-processes of two-way integration: respecting diversity and difference, adopting inclusive practices and striving to achieve equity. Challenges in achieving two-way integration are discussed. Implications for nursing leaders to tap into IENs' diverse talents for the benefit of their local healthcare systems are highlighted.